FACTORS AFFECTING TAX AVOIDANCE IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ikhsan Nur Ilham; Ghazali Syamni; Wahyuddin; Husaini (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to examine the effect of financial distress, leverage, capital intensity and size on tax avoidance in property and real estate companies listed on the Indonesian stock exchange for the 2019-2023 period. The data collection technique uses secondary data in the form of financial reports accessed through the official website www.idx.co.id. The data that has been collected is processed using the STATA 17 programme. The population used in this study are property and real estate companies listed on the Indonesian stock exchange during the 2019-2023 period. The sample selection technique used purposive sampling technique and obtained 17 companies for 5 years with a total sample data obtained was 85 sample data. The data analysis method used in this research is panel data regression analysis. The research results found that, financial distress has no effect on tax avoidance, leverage has a positive effect on tax avoidance, capital intensity has no effect on tax avoidance, and size has a negative effect on tax avoidance in property and real estate companies listed on the Indonesian stock exchange for the period 2019-2023.